Effect of Moisture on Powder Flow Properties of Theophylline - Niklas Sandler; Katharina Reiche; Jyrki Heinämäki; Jouko Yliruusi (MDPI AG, 2010)
Powder flow is influenced by environmental factors, such as moisture and static electricity, as well as powder related factors, such as morphology, size, size distribution, density, and surface area. Pharmaceutical solids may be exposed to water during storage in an atmosphere containing water vapor, or in a dosage form consisting of materials (e.g., excipients) that contain water and are capable of transferring in to other ingredients. The effect of moisture on powder flowability depends on the amount of water and its distribution. The aim of this work was to examine the effect of humidity on the flow properties of theophylline using information derived from solid-state analysis of the systems investigated.